Creating Immersive Learning Experiences With AI: An Android App Approach - Fauzi, Reza; Restendi, Dedi; Nugraha, Firman; Ayundhari, Vidia Lantari (Balai Diklat Keagamaan Bandung, 2024)
This paper explores the development of AI-powered Android-based learning media to enhance immersive learning experiences. Utilizing Design-Based Research (DBR), the study involved the iterative design, development, and evaluation of an interactive Android application. AI tools, including ChatGPT, Quizziz AI, and various image generation software, were embedded to personalize and support the learning process. The app's interactive features, such as quizzes and instant feedback mechanisms, aim to increase learner engagement and motivation. Preliminary testing among trainers highlighted the app's effectiveness in improving user experience and the potential for broader adoption in educational settings. The results suggest that integrating AI into mobile learning platforms can enhance the accessibility and adaptability of educational content. Future research will focus on further app refinements and assessing its long-term impact on student learning outcomes.